Recent development in design a state-of-art proton exchange membrane fuel cell from stack to system: theory, integration and prospective - Fan, Lixin (2023)
As an efficient energy converter, the proton exchange membrane fuel cell (PEMFC) is developed to couple various applications, including portable applications, transportation, stationary power generation, unmanned underwater vehicles, and air independent propulsion. PEMFC is a complex system consisting of different components that can be influenced by many factors, such as material properties, geometric designs operating conditions, and control strategies. The interaction between components and subsystems could affect the performance, durability, and lifespan of PEMFC system. To design a high performance, long lifespan, high durability PEMFC, it's essential to comprehensively understand the coupling effect of different factors on the overall performance and durability of PEMFCs. This review will present existing research on basis of four aspects, involving fuel cell stack design, subsystems design and management, mass transfer enhancement, and system integration. Firstly, the multi-physics intergradation and component design of PEMFC are reviewed with the designing mechanisms and recent progress. Besides, mass transfer enhancement methods are discussed by bipolar plate design and membrane electrode assembly optimization. Then, water management, thermal management, and fuel management are summarized to provide design guidance for PEMFC. The specifications design and system management for various engineering applications are briefly presented.